H46 Huntington and dance. (September 2018) - Salgues, Julie; Chéhère, Philippe; Durr, Alexandra; Gargiulo, Marcela; Bachoud-Lévi, Anne-Catherine; Youssov, Katia; Trinkler, Iris
Abstract : In 2003, Julie Salgues and Philippe Chéhère pioneered Huntington and Dance, series of contemporary dance workshops exploring involuntary movement as a form of artistic practice and research. The relationship to the body is Huntington's involuntary dance, which appear despite oneself without any ability to control it. Created for, and in collaboration with, individuals affected directly or indirectly by Huntington's Disease. The workshops take place at the hospitals Pitié Salpêtrière and Henri Mondor Créteil, at dance studios and art museums in France and Japan, or in the privacy of the patient's home at their request. Methods/approach: The workshops provide a space for relaxation, a space in which to develop one's consciousness. Through creative exercises, we create a space to experiment different ways to move our body; our approach uses the imaginary, the poetic, the inventive and explores multiple sensory modalities. Most importantly however, our approach is artistic and not only therapeutic. In the past 15 years, the experience of workshops have revealed to what extend the practice of contemporary dance can stimulate new ways of relating to oneself and relating to others. We observe how the body posture can be modulated by means of our dance expertise and how in modifying body tonus we change our empathic stance, even the unvoluntary movements. This experience developed through time, allows artists, in quest of a practical, theoretical and creative understanding, to analyze and to witness what Huntington's Disease does to dance, and what our dance does to the illness. Since 2015, some museums have supported our artistic research workshops. For both the involved institutions and dancers, this is a way to integrate patients and reduce social isolation. Outcome: We are currently undertaking a protocol of scientific research (2012–2016), in collaboration with doctors in order to evaluate the influence of the practice of dance for patients. Our dance workshop has been the subject of a randomized controlled pilot study (Trinkler et al. subm.), which found significant improvements of motor function, together with brain plasticity in areas supporting spatial and body processing. Further, the wealth of our experiences have been captured in the documentary Eloge of movement, by David Gil. In sum, over the years we have gathered an enormous amount of evidence of the positive and supportive effect of the 'HD' project on patients, their relatives and their caregivers.